2011
DOI: 10.1007/s00431-011-1626-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pediatric patients with enterovirus meningitis and no cerebral fluid pleocytosis

Abstract: These findings show that EV meningitis occurs in the absence of CSF pleocytosis, particularly in young infants, meaning that EV meningitis in this age group cannot be solely excluded by the absence of CSF pleocytosis. They also confirm the importance of genome detection in the diagnosis of EV meningitis in young infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 29 publications
(44 reference statements)
4
27
0
5
Order By: Relevance
“…In the present study, peripheral WBC was identified as the factors independently influencing CSF pleocytosis. This finding coincides with the recently published data regarding factors associated with CSF pleocytosis in enteroviral meningitis 5 22…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, peripheral WBC was identified as the factors independently influencing CSF pleocytosis. This finding coincides with the recently published data regarding factors associated with CSF pleocytosis in enteroviral meningitis 5 22…”
Section: Discussionsupporting
confidence: 92%
“…All these studies4–6 21 used conventional RT-PCR method for EV detection and applied the first definitions for CSF pleocytosis 7. A recent study22 in The Netherlands showed that 40% (23/58) of children younger than 16 years old with enteroviral meningitis did not have CSF pleocytosis and patients without CSF pleocytosis were younger by use of the conventional RT-PCR method and slightly modified criteria for CSF pleocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, lower peripheral WBC count was significantly related to EVM with CSF non‐pleocytosis. This is in line with recently published studies of CSF non‐pleocytosis in EVM …”
Section: Discussionsupporting
confidence: 92%
“…In addition, shorter interval from symptom onset to LP, lower CSF protein, and lower WBC count and CRP were significantly associated with EVM with CSF non‐pleocytosis on univariate analysis. Although there have been a few reports of young infants and children with EVM accompanied by CSF non‐pleocytosis, the present study is the first to investigate the clinical and laboratory findings, seasonality, and outcomes of CSF non‐pleocytosis using large‐scale data, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Empiric antibiotic treatment was given to only 9% of children in our hospital in 2009, compared to 76–100% in other studies [4], [17], good evidence of the extensive experience of the pediatricians taking part in our study. Being certain of obtaining results by the end of the day, these pediatricians discharged more than one child in two from the hospital before receiving the results of the positive EV molecular test.…”
Section: Discussionmentioning
confidence: 50%